seven times a two digit number is equal to four times the number obtained by reversing the order of its digits if the difference between the digits is 3 , find the number

let the two digit no. be  10x + y 

then 7 (10 x +y) = 4(10y + x)          ------------> 70 x + 7y = 40y + 4x               -------> 66x = 33y  ----------> y = 2x .....(1)

y -x = 3     ....(2)

2x -x =3  (substitute the value of y from (1) )

  x =3 

or, y -3=3         y = 6

so the no.  10x +y = 10*3 + 6 = 30 +6 = 36

 

 

 

 

 

 

 

 

     

  • 29

LET THE DIGIT AT TEN" S PLACE BE X & UNIT"S PLACE BE Y

REQ. ORIGINAL NO. = 10X+Y  REVERSED NO.  =10Y+X

ALSO Y - X = 3 =>   Y = 3 +X

A/Q,  7(10X+Y)  =  4 (10Y+X)

=> 7( 11X + 3)  =  4( 30  +11X)

=>77X -44X  =  120 -21

=>  33 X  =99 

=> X =  3  &  Y= 3 +X  =  3 +3  = 6 

REQ. ORIGINAL NO. = 10X+Y  =  10 *  3  +6  =  36...................

  • 89
I DONT KNOW
  • -47
jh
  • 20
yo bro
 
  • -30
Dope
  • -26
Let y be in ten's place and x be in one's place. So the number is 10y+x. Then the reversed number is 10x+y
7(10y+x) = 4(10x+y)
70y+7x    = 40x+4y
​Transposing 70y+7x to RHS
33x-66y  = 0
Dividing by 33
x-2y = 0.             1
x-y   = 3.              2
x      =  3+y
Substituting x in 1
3+y-2y = 0
         -y = -3

We cancel (-) sign from both LHS and RHS
​          y=3
Substituting y= 3 in 1
x-2×3  = 0
      x   = 6
Therefore the required number is 36.




Thanks please give a thumbs up if this helped you.

 
  • 7
dekh bhai pdahe me kuch nhe rakha hai... chodh es sabh ko masti fun kr
  • -26
Sfv

  • 1
Seven times a given two digit number is equal to four times the number obtained by inter changing the digits
7(10x+y)=4(x+10y)
70x+7y=4x+40y
66x-33y=0
2x-y=0
2x=y
The difference of the digits is 3
y-x=3
2x-x=3
x=3
y=6
that number is 36. sunil Bhardwaj
  • 15
Cheers!!

  • 3
Hope it will help

  • -1
No:10x+y Reversing:10y+x 7(10x+y)=4(10y+x) 70x+7y=40y+4x 66x=33y 66x-33y=0 2x-y=0 2x=y••••••eq(1) Given y-x=3•••••eq(2) Sub eq (1)in eq(2) 2x-x=3 X=3 y-x=3 y-3=3 y=3+3=6👍👍👍
  • -2
By Samridhi

  • 1
Like please

  • 1
Why did we take y as greater????
  • -1
how can u assume that y is greater than x
it should be taken in two cases
one that y is less than x and another that y is greater than x.
if y is less than x we get x as -3 (which is not possible)
 
  • 1
Here is the answer

  • -1
What are you looking for?